Development of the Sepsis-Associated Adverse Outcomes in Pregnancy Score - Stephens, Angela J.; Lee, Kyung H.; Barton, John R.; Chauhan, Suneet P.; Baker, Andrea L.; Sibai, Baha M. (American Journal of Perinatology, 2022)
Objective This study aimed to develop and evaluate a scoring system—called the Sepsis-Associated Adverse Outcomes in Pregnancy (SAAP) Score—to identify individuals with maternal infection that have composite maternal adverse outcomes (CMAO).Study Design Using the International Classification of Disease codes, we identified pregnant and postpartum (up to 6 weeks after birth) individuals admitted at our center with a primary diagnosis of infection. The primary outcome was CMAO which included any of the following: maternal intensive care unit admission, surgical intervention, vasopressor use, acute respiratory distress syndrome, pulmonary edema, mechanical ventilation, high-flow nasal cannula, disseminated intravascular coagulation, dialysis, organ failure, venous thromboembolism, or maternal death. Regularized logistic regression was used to identify variables that best discriminate CMAO status. Variables were chosen for inclusion following evaluation of statistical and clinical significance. Model performance was evaluated using area under the curve (AUC) with 95% confidence intervals (CIs), sensitivity, specificity, and predictive values.Results Of the 23,235 deliveries during the study period, 227 (0.9%) individuals met inclusion criteria and among them CMAO occurred in 39.2% (95% CI: 33.1–45.7%). The SAAP score consisted of six variables (white blood cell count, systolic blood pressure, respiratory rate, heart rate, lactic acid, and abnormal diagnostic imaging) with scores ranging from 0 to 11 and a score of ≥7 being abnormal. An abnormal SAAP score had an AUC of 0.80 (95% CI: 0.74–0.86) for CMAO. The sensitivity and specificity of the SAAP score for CMAO was 0.71 (95% CI: 0.60–0.80) and 0.73 (95% CI: 0.64–0.80), respectively. The positive predictive value was 0.62 (95% CI: 0.52–0.72) and negative predictive value was 0.79 (95% CI: 0.71–0.86).Conclusion Pending external validation, the sixth variable SAAP score may permit early recognition of pregnant and postpartum individuals with infection who are likely to develop adverse maternal outcomes.Key Points
Keywords: sepsis; maternal sepsis; sepsis in pregnancy; maternal morbidity; maternal mortality